2015
DOI: 10.4172/2168-9296.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Moderator Bands (Trabecula septomarginalis) of Mature Buffalo (Bos bubalis L.) with Special Emphasis on the Structure and Distribution of the Purkinje Cardiomyocytes: Histological and Histochemical

Abstract: Ten hearts of mature healthy Buffalo (Bos bubalis L.) were employed to investigate the histological and histochemical structures of the moderator bands. Hearts were gently dissected and the moderator bands were collected. The specimens were processed histologically and subjected to different stains. Grossly, the moderator band (Septomarginal trabeculae) was a single muscular band that was found only in the right ventricle of the buffalo heart. It extended from the interventricular septum to the free ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…In the present study, the septomarginal trabeculae of the bovine heart were a single muscular band that extends from the interventricular septum to the opposite right ventricular wall. It is in accordance with findings in studies using others species, such as pigs (Ateş et al, ; Gulyaeva & Roshchevskaya, ), dogs (Bombonato et al, ; Cope, ), camels (Ghonimi, Abuel‐Atta, Bareedy, & Balah, ), equines (Ghonimi et al, ; Halıgür & Dursun, ; Sathyamoorthy & Ramesh, ) and humans (Bandeira et al, ; Kosiński et al, ; Mamatha et al., ; Reig, Alberti, & Petit, ; Rocha et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the septomarginal trabeculae of the bovine heart were a single muscular band that extends from the interventricular septum to the opposite right ventricular wall. It is in accordance with findings in studies using others species, such as pigs (Ateş et al, ; Gulyaeva & Roshchevskaya, ), dogs (Bombonato et al, ; Cope, ), camels (Ghonimi, Abuel‐Atta, Bareedy, & Balah, ), equines (Ghonimi et al, ; Halıgür & Dursun, ; Sathyamoorthy & Ramesh, ) and humans (Bandeira et al, ; Kosiński et al, ; Mamatha et al., ; Reig, Alberti, & Petit, ; Rocha et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Studies on the location of moderator bands and the distribution of conductive cells in those structures have been conducted in humans (Bandeira et al, ; Chaudhary, Bharti, & Deshpande, ; Kosiński et al, ; Mamatha, Shenoy, D´Souza, Prasana, Sumalatha, Shenoy, D´Souza, Prasanna, & Sumalatha, ; Rocha et al, ; Shenoy, Lucas, Vinay, & Ramos, ) and several animal species, including goats (Leão et al, ), sheeps (Ansari, Ho, & Anderson, ), pigs (Bojsen‐Moller & Tranum‐Jensen, ; Gulyaeva & Roshchevskaya, ), dogs (Bombonato et al, ), equines (Bombonato et al, ; Sathyamoorthy & Ramesh, ), buffalos (Ghonimi et al, ) and ostriches (Parto, Tadjalli, & Ghazi, ). Meanwhile, not many studies involving morphology, tissue morphological composition and possible variations of the septomarginal trabecula were performed.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the histological examination of the ST revealed the presence of connective tissue, cardiac muscle fibers, blood vessels, and Purkinje cells in pig heart samples, in agreement with the histological description of the trabeculae in other animal species and in humans 11,16,17,19,32,[43][44][45][46] . It was also evidenced a variation in Purkinje fibers distribution and disposition, besides the proportion between the striated cardiac and connective muscle tissues between the samples.…”
Section: Discussionsupporting
confidence: 88%
“…In the literature, it has been reported that the right septomarginal trabecula extends between the septum—outer wall (Evans & De Lahunta, 2013; Nascimento et al, 2019; Ravindran & Victor, 1982) septum—anterior papillary muscle (Ghonimi et al, 2015; Kosinski et al, 2010; Leao et al, 2010; Nascimento et al, 2019; Raghavendra et al, 2013), anterior papillary muscle—outer wall (Arıncı & Elhan, 2014; Ateş & Çakır, 2010; Cope, 2016b; Evans & De Lahunta, 2013), and septal papillary muscle—anterior papillary muscle (Ates et al, 2017; Gulyaeva & Roshchevskaya, 2012; Perez et al, 2018). In our study, it was determined that the right septomarginal trabecula extended between the septal papillary muscle and the anterior papillary muscle.…”
Section: Discussionmentioning
confidence: 99%